FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zahara Fatimah; Ni Made Artini (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
This research aims to know empirical evidence as for factors influencing timeliness of financial reporting or the manufacture firm listed in Indonesia Stock Exchange. The factors to be análysised in this research namely debt to equity ratio, profitability (ROA), ownership structure, quality of auditor (KAP), and auditor change. Sample of this research is 375 manufacture firms listed in Indonesia Stock Exchange period 2008-2012 that selected by using purposive sampling method. Technique of anáyisis for examining the hipótesis was logistic regresión at level significance 5%. Result of this research identify that profitability (ROA) and ownership structure significantly affect timeliness of financial reporting of the firm, whereas debt to equity ratio, quality of auditor (KAP), and auditor change not have an affect to timeliness of financial reporting of the firm listed in Indonesia Stock Exchange.